Evaluation of commercial chromogenic media for the detection of meticillin-resistant Staphylococcus aureus. Issue 3 (March 2016) - Brennan, G.I.; Herra, C.; Coleman, D.C.; O'Connell, B.; Shore, A.C.
Summary: Background: Selective chromogenic media allowing one-step meticillin-resistant Staphylococcus aureus (MRSA) isolation and identification are widely used. However, the changing epidemiology of MRSA means that the suitability of these chromogenic media requires investigation. Aim: To evaluate the following chromogenic media – Colorex MRSA, MRSA Select II, ChromID MRSA, and MRSA Brilliance 2 – for the detection of divergent strain types. Methods: We used a diverse collection of S. aureus, including strains harbouring the mecC gene, strains expressing varying levels of meticillin resistance, and isolates recovered from patient samples. Findings: MRSA Select II, Colorex MRSA, and ChromID each grew at a density of 1.5 × 10 1  cfu/mL for each SCC mec type investigated. Brilliance 2 demonstrated growth at 1.5 × 10 1  cfu/mL for mecC MRSA but at a higher density (1.5 × 10 4  cfu/mL) for the three mecA MRSA strains. All four media demonstrated excellent sensitivity for MRSA detection (≥99%), but reduced levels of specificity (85–73%) when challenged with a range of meticillin-susceptible S. aureus (MSSA) isolates. High levels of false positives (∼50%) were also obtained with all chromogenic media when tested with mec -negative borderline oxacillin-resistant S. aureus (BORSA) isolates. Conclusion: Although false positives may be obtained with some strains of MSSA and BORSA, the high sensitivity of these media and their ability to recover almost all MRSA tested (including oxacillin-susceptible and mec C-positive strains) confirm the value of chromogenic agar in MRSA detection.